Internal ribosome entry site drives cap-independent translation of reaper and heat shock protein 70 mRNAs in Drosophila embryos. - Hernandez, G.; Vazquez-Pianzola, P.; Sierra, J.M.; Rivera-Pomar, R. (RNA (New York, N.Y.), 2004)
Translation is a sensitive regulatory step during cellular stress and the apoptosis response. Under such conditions, cap-dependent translation is reduced and internal ribosome entry site (IRES)-dependent translation plays a major role. However, many aspects of how mRNAs are translated under stress remain to be elucidated. Here we report that reaper mRNA, a pro-apoptotic gene from Drosophila melanogaster, is translated in a cap-independent manner. In Drosophila mutant embryos devoid of the eukaryotic initiation factor 4E (eIF4E), reaper transcription is induced and apoptosis proceeds. In vitro translation experiments using wild-type and eIF4E mutant embryonic extracts show that reporter mRNA bearing reaper 5' untranslated region (UTR) is effectively translated in a cap-independent manner. The 5'UTR of reaper exhibits a high degree of similarity with that of Drosophila heat shock protein 70 mRNA, and both display IRES activity. Studies of mRNA association to polysomes in embryos indicate that both reaper and heat shock protein 70 mRNAs are recruited to polysomes under apoptosis or thermal stress. Our data suggest that heat shock protein 70 and reaper, two antagonizing factors in apoptosis, use a similar mechanism for protein synthesis.